2023
DOI: 10.3390/biomedicines11082177
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Hyperpolarization-Activated Cation Currents through Small Molecule Perturbations: Magnitude and Gating Control

Abstract: The hyperpolarization-activated cation current (Ih) exhibits a slowly activating time course of the current (Ih) when the cell membrane is hyperpolarized for an extended duration. It is involved in generating electrical activity in various excitable cells. Numerous structurally distinct compounds or herbal drugs have the potential to impact both the magnitude and gating kinetics of this current. Brivaracetam, a chemical analog of levetiracetam known to be a ligand for synaptic vesicle protein 2A, could directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Additionally, a deeper understanding of dexmedetomidine's interaction with HCN channels may offer new insights into managing various pain conditions that involve modulation of neuronal excitability. 29,30 There are still some limitations in the current study. While forskolin has been extensively employed as an enhancer of HCN channels through the elevation of cyclic AMP levels, it is noteworthy that cAMP, a second messenger, may elicit additional effects.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, a deeper understanding of dexmedetomidine's interaction with HCN channels may offer new insights into managing various pain conditions that involve modulation of neuronal excitability. 29,30 There are still some limitations in the current study. While forskolin has been extensively employed as an enhancer of HCN channels through the elevation of cyclic AMP levels, it is noteworthy that cAMP, a second messenger, may elicit additional effects.…”
Section: Discussionmentioning
confidence: 92%
“…In recent research conducted on pituitary GH 3 cells, it was demonstrated that exposure to CBD leads to the suppression in the amplitudes of I K(M) and the hyperpolarization-activated cation current (I h ), with the corresponding IC 50 values of 3.6 and 3.3 µM, respectively [14]. The biophysical property of I h is distinctive, marked by its slow activation kinetics during sustained hyperpolarization [38,39]. Furthermore, given CBD's impact on ion channels situated on the cell membrane, it appears unlikely that these effects can be solely ascribed to CBD's interaction with cannabinoid receptors.…”
Section: Cannabidiol (Cbd)mentioning
confidence: 99%